A Study on the Application of Automatic Scoring and Feedback System in College English Writing - Lv, Xiaoxiao (International Journal of Emerging Technologies in Learning (iJET), 2018)
With the rapid development of computer technology and the need of college Eng-lish teaching, the automatic grading of college students’ English writing level is an inevitable trend. This is the inevitable result of the combination of computer tech-nology and English teaching. The theoretical basis of this paper is the feedback of English writing and related theories introduced as follows. This paper analyzes the influence of automatic scoring and feedback system on English writing level via testing the variation of student composition’s grammar, structure, length and grade in a teaching experiment. The experimental results indicate that online feed-back is effective in evaluating students’ English writing proficiency, which can help students improve their writing proficiency and independent writing ability. The students’ attitudes and views towards automatic grading and feedback system were investigated with 118 students in the English experiment class of SUST as the test object. The research results can suggest a guide line in the improvement of college students’ writing competence and evaluation of the effect of automatic scoring feedback system.